Aspectos bioecológicos de Euschistus heros (Fabricius, 1798) (Heteroptera : Pentatonidae), em Euphorbia heterophylla Linnaeus (Euphorbiaceae) e Glycine marx (L.) Merril (Leguminosae) - Pinto, Simone Benghi (1993)
Orientador: Dr. Antonio Ricardo Panizzi